Transport in Human Scale Cities (Edward Elgar Publishing, 2021)
This timely book calls for a paradigm shift in urban transport, which remains one of the critically uncertain aspects of the sustainability transformation of our societies. It argues that the potential of human scale thinking needs to be recognised, both in understanding people on the move in the city and within various organisations responsible for cities.